Involvement of Felis catus papillomavirus type 2 in the tumorigenesis of feline Merkel cell carcinoma. Issue 1 (January 2022) - Ito, Soma; Chambers, James K.; Sumi, Ayumi; Yamashita-Kawanishi, Nanako; Omachi, Tetsuo; Haga, Takeshi; Nakayama, Hiroyuki; Uchida, Kazuyuki
Merkel cell carcinoma (MCC) is a cutaneous neuroendocrine tumor. We recently demonstrated that cats with MCC often have other proliferative cutaneous lesions, such as squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). Based on this finding, we hypothesize that Felis catus papillomavirus (FcaPV) is involved in the development of MCC in cats, similar to SCC and BCC. To investigate this hypothesis, the presence of FcaPV nucleic acid and immunoreactivity for tumor suppressor proteins were examined in 21 feline MCC cases. Polymerase chain reaction using FcaPV type-specific primers detected FcaPV2 DNA in 20/21 samples of MCC. The complete FcaPV2 sequence was characterized in one case. In situ hybridization for FcaPV2 E7 revealed punctate nuclear signals within tumor cells in 19/21 MCC. Increased immunoreactivity for p16 CDKN2A protein and decreased immunoreactivity for retinoblastoma (pRb) and p53 proteins were observed in 20/21 MCC. These results suggest that feline MCC cases are infected with FcaPV2 and the subsequent inhibition of pRb and p53 induced by integrated viral oncogenes is associated with feline MCC tumorigenesis, similar to other PV-induced proliferative cutaneous lesions. On the other hand, the single case of FcaPV2-negative MCC showed strong p53 immunoreactivity, suggesting mutations in p53 caused by cancer inducers other than FcaPV2 infection in this case. The present study suggests FcaPV2 as a cause of feline MCC.